“The Lapps are used like camels in distant lands":Sámi research in the northernmost parsonage of Finnish Lapland - Kylli, R. (Ritva) (Northern Arctic Federal University, 2017)
Abstract Anders Andelin was a Finnish clergyman who engaged in Sámi research in the northernmost parsonage of Finland in the 1850s. His efforts were not exceptional, as the residents of 19th century European rural parsonages practiced a lot of research. Andelin himself was an amateur ethnographer, historian, archaeologist, meteorologist, geographer, natural scientist, linguist, and toponymist. He was, as a Sámi researcher, between old and new scientific traditions: The middle of the nineteenth century has been regarded as a turning point in the history of academic research in Finland. Until then, researchers collected folklore, historical sources, plants, and meteorological observations. Around the 1850s the focus shifted from collecting and listing towards more analytical and experimental research. Andelin published his writings in scientific journals but also compiled a lot of detailed information related to the Sámi people, as the Sámi were thought to be a primitive people heading towards extinction. The clergymen who came to Lapland also viewed the Sámi lands through the lens of cultivation. They gathered statistics, which could be used to justify the need for the efforts of agriculture in Lapland.